2013 IEEE International Symposium on Parallel &Amp; Distributed Processing, Workshops and PHD Forum 2013
DOI: 10.1109/ipdpsw.2013.108
|View full text |Cite
|
Sign up to set email alerts
|

Simplify: A Framework for Enabling Fast Functional/Behavioral Validation of Multiprocessor Architectures in the Cloud

Abstract: The design of high-performance Multiprocessor Systems-on-Chip (MPSoCs) has proven to be an attractive challenge in embedded systems design automation. However, the complexity of such designs associated with short timeto-market constraints impose serious limitations on the exploration of different configurations and scenarios on the design space exploration. The use of virtual platforms may decrease the time-to-market of these architectures while providing the means to exploit, debug and verify architectures wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…A platform is modelled through the following sets of APIs: The use of OVP to model heterogeneous multiprocessor architectures is described in [17] through a set of case studies. A drag and drop interactive approach for MPSoC exploration using OVP is proposed in [18]. A technique exploiting OVP for development and optimization of embedded computing applications by handling heterogeneity at the chip, node, and network level is proposed in [19].…”
Section: Ovpmentioning
confidence: 99%
See 1 more Smart Citation
“…A platform is modelled through the following sets of APIs: The use of OVP to model heterogeneous multiprocessor architectures is described in [17] through a set of case studies. A drag and drop interactive approach for MPSoC exploration using OVP is proposed in [18]. A technique exploiting OVP for development and optimization of embedded computing applications by handling heterogeneity at the chip, node, and network level is proposed in [19].…”
Section: Ovpmentioning
confidence: 99%
“…At platform level, a signal is used to connect the virtual device to the interrupt lines provided by the platform chipset (line 36). When an interrupt is generated by the SystemC device, the interrupt is notified to the chipset through such a signal (lines [18][19]. To catch the interrupt from the SystemC module, the virtual device creates an OVP thread (line 40-41) that cyclically checks the is_ready line of the SystemC module (lines 1-21).…”
Section: Interrupt Handlingmentioning
confidence: 99%
“…Authors in [3] have observed that applications running on different processors have significant differences in performance. Therefore, chosen an appropriate processor, or a set of them, to execute the GA might be very Besides that, the OVP uses cross-compilers directly coupled with the target processor, which makes it possible that applications previously compiled to OVP can easily run on hardware architectures without the need of porting the code.…”
Section: Virtualization Of the Standard Ga On Ovpmentioning
confidence: 99%
“…The use of OVP to model heterogeneous multiprocessor architectures is described in [13] through a set of case studies. A drag and drop interactive approach for MPSoC exploration using OVP is proposed in [14]. A technique exploiting OVP for development and optimization of embedded computing applications by handling heterogeneity at the chip, node, and network level is proposed in [15].…”
Section: B Ovpmentioning
confidence: 99%